2020
DOI: 10.1152/jn.00590.2019
|View full text |Cite
|
Sign up to set email alerts
|

Role of deep breaths in ultrasonic vocal production of Sprague-Dawley rats

Abstract: Deep breaths are one of three breathing patterns in rodents characterized by an increased tidal volume. While humans incorporate deep breaths into vocal behavior, it was unknown whether nonhuman mammals use deep breaths for vocal production. We have utilized subglottal pressure recordings in awake, spontaneously behaving male Sprague-Dawley rats in five contexts: sleep, rest, noxious stimulation, exposure to a female in estrus, and exposure to an unknown male. Deep breaths were produced at rates ranging betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Moreover, little is still known about sex differences in the acoustic features of 22-kHz USV and few data on 22-kHz USV recorded under standardized conditions in response to air puffs or electric foot shocks are available. It is currently unclear whether such sex differences simply reflect anatomical differences between males and females, such as body weight, lung capacity and vocal tract length (Hegoburu et al, 2011;Inagaki et al, 2012;Riede et al, 2020), or whether they serve communicative functions, for instance through providing additional features by which listening conspecifics may be able to determine the sex of the vocalizing rat, as suggested by Blanchard et al (1992).…”
Section: Sex Differences In the Production Of Alarm 22-khz Usvmentioning
confidence: 99%
“…Moreover, little is still known about sex differences in the acoustic features of 22-kHz USV and few data on 22-kHz USV recorded under standardized conditions in response to air puffs or electric foot shocks are available. It is currently unclear whether such sex differences simply reflect anatomical differences between males and females, such as body weight, lung capacity and vocal tract length (Hegoburu et al, 2011;Inagaki et al, 2012;Riede et al, 2020), or whether they serve communicative functions, for instance through providing additional features by which listening conspecifics may be able to determine the sex of the vocalizing rat, as suggested by Blanchard et al (1992).…”
Section: Sex Differences In the Production Of Alarm 22-khz Usvmentioning
confidence: 99%
“…It should be mentioned, though, that the advances in research techniques have now made it possible to study this possibility in more detail and resulted in the conclusion that USVs are not just simply a byproduct. Evidence showed that the emitted USVs are indeed tightly linked to locomotion [25], breathing [44] and cardiovascular function [43], and they are even interlocked with active sniffing [45].…”
Section: Discussionmentioning
confidence: 99%
“…and a new call type can be started at any point during the exhalation phase [44,46,47]. It should be taken into account, though, that if USVs are more than just a by-effect of arousal, there should be more information in nuances of the vocal communication, as they have an extensive USV 'vocabulary' [48,49]).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, USV are emitted during the expiratory phase of the respiratory cycle [ 12 , 64 , 104 , 105 , 106 ]. In the 22-kHz USV of adult rats, the length of the expiratory phase is correlated with the length of the USV and is significantly longer than the silent expiratory phases [ 4 , 12 ], suggesting that emitting USV lengthens the expiratory phase, and it is possible that the USV duration is limited by the physiological need to breathe [ 107 ]. Similarly, longer lower-frequency infantile USV are also correlated in length with the expiratory phase of the respiration [ 4 ].…”
Section: Ethological and Anatomical Considerations For The Emission Of Usvmentioning
confidence: 99%